PALLIATIVE AND HOSPICE SERVICES IN LONG TERM CARE. (11th November 2018) - Harrison, T; Blozis, S; Dionne-Vahalik, M; Mead, S
Abstract: Our purpose is to explore perceived satisfaction with pain management among residents of long-term care (LTC) facilities, with hospice/palliative care (HPC) hypothesized to improve services. The 22 RNs used tablets to review charts; speak to facility administrators, and interview residents / family. Analyses included random-effects logistic model. We explored data from 815 LTC facilities using within facility, random selection of 1, 412 residents. The results indicate that 147 or 10% of residents receive HPC. Regarding pain care satisfaction, 989 residents responded to the question and 159 (16%) were not satisfied; 830 were satisfied (84%). The estimated average probability of being satisfied with pain relief was .839 (se = .012, 95% CI: 0.816, 0.862). We also found no difference in the satisfaction with pain relief for HPC users and not. The estimated effect of HPC on the logit was -0.09225 (se=0.2980), p-value = 0.7570, 95% CI of the effect: (-0.6771 0.4926). For reported minutes taken to receive medication after the request, 570 residents responded to the question. Estimated variation in log-transformed time spent was attributed to facilities. The estimated proportion was 0.3673/(0.3673 + 0.7798) = .32 No differences found in reported time to receipt of medication after request for HPC and not. The estimated effect of HPC on reported time was 0.03862 (se=0.2086), p-value = 0.8532, 95% CI of the effect: (-0.3712, 0.4485)). Overall, the majority of residents are satisfied with their pain control; variation was due to individual facility differences. Hospice/palliative care had no effect on the satisfaction or time to medication.